Aligning business leadership development with business needs: the value of discrimination - Bailey, Catherine; Clarke, Martin (Emerald Group Publishing Limited, 2008)
Abstract Purpose – This paper is derived from a two-year study that sought to provide a critical understanding of the current state of business leadership development (BLD) and to identify directions for innovative future practice. The first of two companion papers, this contribution aims to examine the issue of achieving business relevance in BLD and the quality of HR/management development strategy formulation. Design/methodology/approach – The paper analyses four organisation case studies of BLD strategy derived from interview data sourced from 103 senior line/HRD managers in 20 organisations. Findings – The findings highlight the need for HRD managers to take a discriminating approach to linking BLD strategy, development method, evaluation and the role of management development. In particular, the cases studied reflect the importance of informal activity and politics in the execution of BLD and the positive effect of individual leadership in moderating the effectiveness of the linkages between business context, BLD strategy and its implementation. Practical implications – The paper provides a conceptual framework to enable practitioners to discriminate between different bundles of development practices that can, over time, be translated into behaviours that suit the changing needs of an organisation. A list of useful starting points is provided for managers to review and improve BLD strategy and practice in their own organisation. Originality/value – The paper provides a framework that shows the importance of different development populations, different sponsors, interest groups and strategic timeframes in enabling more informed discussion about the strategic alignme
Keywords: MT=GENERAL; Integration; Leadership; Organizational politics; Human resource development; Management strategy